Catalytic C–H amination at its limits: challenges and solutions. Issue 12 (12th September 2017) - Hazelard, Damien; Nocquet, Pierre-Antoine; Compain, Philippe
Abstract : Pushing C–H amination to its limits fosters innovative synthetic solutions and offers a deeper understanding of the reaction mechanism and scope. Abstract : Catalytic C–H amination reactions enable direct functionalization of non-activated C(sp 3 )–H bonds with high levels of regio-, chemo- and stereoselectivity. As a powerful tool to unlock the potential of inert C–H bonds, C–H amination chemistry has been applied to the preparation of synthetically challenging targets since major simplification of synthetic sequences are expected from this approach. Pushing C–H amination to its limits has led to a deeper understanding of the reaction mechanism and scope. In this review, we present a description of the specific challenges facing catalytic C–H amination in the synthesis of natural products and related compounds, as well as innovative tactics created to overcome them. By identifying and discussing the major insights gained and strategies designed, we hope that this review will stimulate further progress in C–H amination chemistry and beyond.